Pengaruh Faktor-faktor dalam Teori Fraud Pentagon terhadap Kecurangan Laporan Keuangan pada Perusahaan BUMN Periode 2014 – 2018 - Brilianti Husnul Khotimah; Andi Asrihapsari; Bandi Bandi (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2020)
This research is to find evidence about pentagon fraud theory, which are proxied by financial target; financial stability; level of supervision’s effectiveness; rationalization; board of commissioners’ age; and frequency of CEO photos, of fraudulent financial statements which is proxied by Dechow F-Score model. Samples tested were 63 samples from government companies during the period 2014 - 2018. The results are financial statement fraud is positively influenced by financial stability and rationalization, and negatively influenced by level of supervision’s effectiveness. While the other three variables have no effect.